Indonesia’s Efforts as a Transit Country in Handling Irregular Migration through the Bali Process - Wibowo, Gloria; Yazid, Sylvia (Jurnal Indonesia Sosial Sains, 2024)
Migration, or the movement of people from their country of origin to another country, is not a new phenomenon in human life. Transnational crime occurs not only due to free trade factors and weak law enforcement but also due to the geographical conditions of the country itself. This research aims to analyse and determine Indonesia's efforts to handle irregular migration as an implementation of the Bali Process. This research uses a type of qualitative research that is descriptive analysis. The data collection techniques used in this research are secondary documents and internet-based techniques. The results of the research show that Indonesia's efforts to deal with irregular migration can be carried out with preventive and repressive efforts as stated in Article 89, paragraphs 1. 2, and 3. Cooperation between Indonesia and Australia to deal with irregular migration in the Bali Process has resulted in several equal partnerships in an MOU. Efforts to handle and protect irregular migration in the Bali process are carried out by taking into account the policies of each country with a comprehensive regional approach in accordance with the principles of Burden sharing and collective responsibility. Cooperation between Australia and Indonesia uses the basic assumptions contained in the theory of institutional liberalism put forward by Robert Keohane and Joseph Nye, in the form of: 1. Trust in Cooperation, 2. International regime, 3. Complex dependency, and 4. Interdependence.